(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
Islamism is a religious and political phenomenon that has spread worldwide and, as such, has been extensively dealt with in literature, knowledge of which serves to assess its cultural significance in a fairer dimension. Ibn Ŷubayr, an important Almohad official, arbiter and teacher of Islamic subjects, was one of the first and the highest exponent of the genre of the Rihla or travel narratives in the Arabic language. In his work Through the East, he recounts his journey from AlAndalus to the Hijaz and back, as part of his pilgrimage to the holy places of Islam between 1181 and 1183. This article highlights the literary value of Ŷubayr’s prolix account of the life experiences of his travels, the immersion and contact with other landscapes and cultures, the political contexts in which they unfolded, and the way in which these experiences affected his sensibility. All this is masterfully reflected in his way of recounting the vicissitudes of this journey, in a way that makes his account pertinent, interesting and instructive for the contemporary scholar.